Novos campi públicos brasileiros : concepções projetuais - Oliveira, Liliane Torres de (2009)
This research project on the plans of the new campuses for Brazilian public Universities aims to discuss the urbanistic proposals used in four different plans in the state of Sao Paulo. This work attempts to evince which concepts were adopted in these projects, taking into account the national context, at the beginning of this century, of expansion, creation and restructuring of new campuses for public Universities and the relevance that this urban equipment has because of its social function and dimension. As theoretical foundation, we present a survey of historical moments that are of major concern for the apprehension of the research object. To this end, we approach initially the birth of the first University in Europe and the emergence of the campus in the U.S.A. Then, dealing with the history of Brazilian Universities, we highlight the development process of the campus, taking into consideration that the beginning of its implementation is an essential and paradigmatic phase. In order to discuss the proposals for the four new plans, certain categories of analysis were established, which focus on: an analysis of site where the campus is placed, the identification of urbanistic concepts, the parameters and guidelines for urban design, the verification of the road system, a spatial analysis of buildings and the open area and, finally, environmental sustainability a current theme present in disputes on planning. By means of systematization of the collected data, we sought to identify the urbanistic performance and the similarities and differences between the plans. Various issues were found in the specificities of each plan, such as the production of spaces that meet the new pedagogical proposals, the appreciation of the collective use of spaces for both convivence and learning, the promotion of environmental sustainability and the accessibility and mobility on the campuses, which demonstrates that there is an intent to match the demands generated by contemporary society.